Investigational drugs in systemic vasculitis. (2nd September 2017) - Mirouse, Adrien; Cacoub, Patrice; Desbois, Anne Claire; Comarmond, Cloé; Pagnoux, Christian; Saadoun, David
ABSTRACT: Introduction : Treatment of systemic vasculitis is based on glucocorticoids (GC) in association with immunosuppressive therapy. There are still unmet needs, including earlier onset of response, more targeted therapies, reduction of relapse-risk and decrease of long-term GC and classic immunosuppressants toxicities. Areas covered : In this review, we discuss investigational drugs in early phase clinical trials for induction of remission in vasculitis. We focus on ANCA-associated vasculitis, Behçet's disease, giant cell arteritis, Takayasu arteritis, and cryoglobulinemic vasculitis. We performed a comprehensive review of articles published on pubmed and a review of clinical trials registered online (https://clinicaltrials.gov ) for each vasculitis. Expert opinion : Recent progress in the pathogenesis identifies new therapeutic targets. Some of these therapies are promising in GC sparing effects, in reducing relapse rate, and for their safety profile. These results need to be confirmed in large-scale phase III studies.